CURCUMIN, A POTENT ANTICARCINOGENIC POLYPHENOL – A REVIEW - STEFFI.P.F; M, SRINIVASAN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Turmeric the common name for Curcuma longa is an Indian flavor inferred from the rhizomes of the plant and has a long history of utilization in Ayurvedic medication. Curcumin, the principal curcuminoid found in turmeric, is in general considered its most active constituent. Curcumin, a standout amongst the most widely used natural active constituents with a great variety of beneficial biological and pharmacological activities, is a basically water-insoluble substance with a short biologic half-life. Extensive research has addressed the chemopreventive potential of this non toxic polyphenol. The anticancer potential of curcumin is resolved from its ability to suppress proliferation of a wide variety of tumor cells, down regulate transcription factors NF-κB, AP-1 and Egr-1; down-regulate the expression of COX-2, LOX, NOS, MMP-9, uPA, TNF, chemokines, cell surface adhesion molecules and cyclin D1; down-regulate growth factor receptors (such as EGFR and HER2); and inhibit the activity of c-Jun N-terminal kinase, protein tyrosine kinases and protein serine/threonine kinases. This review will summarize the unique properties of curcumin that may be exploited for successful cancer prevention. Keywords: Turmeric, Curcuma longa, Chemopreventive, Curcumin, Polyphenol, Anticancer activity.